Formulation And Characterization Of Porcelain Balls From Malaysia Clays - Yahya, Hamdan (2016)
The aim of this research is to fabricate locally produced low sintering temperature porcelain balls as grinding media with superior mechanical and physical properties than the similar commercially available grinding media. The mostly used grinding media is steel balls especially for mineral processing for reduction of particles sizes; however, it is not suitable for pharmaceutical and cosmetic industries due to contamination of iron. Therefore, porcelain balls are one of the alternative media that can substitute this steel grinding media due to its high chemical stability and wear resistant. However, Malaysian industries are solely dependent on the imported ceramic balls. Therefore, this research on locally produced ceramic balls using processed Malaysian clays was initiated. The research is divided into three parts i.e. Part I is on characterization of the five selected processed Malaysian clays, Part II deals on the evaluation the five formulated local porcelain bodies based on PBT, PBC, PBP, PBS and PBB, which used clays from Trong, Kg. Coldstream, Simpang Pulai, Selendang and Bidor, respectively. Part III deals with the grinding properties of the selected local porcelain body formulation (PBT) which was tested for wear and tear tests for milling performance and compared to the commercial porcelain balls. Results showed that physical and mechanical properties of local porcelain bodies were increased with sintering temperature whereby PBT body sintered at 1270 °C shows the highest hardness (7.32 GPa) and compressive strength (381.6 MPa). The milling performance results showed that PBT balls has five times greater wear resistance is only at 2.44% whereas 13.49% for CPB (commercial porcelain balls) and 10% better milling performance of particles size reduction than CPB. This research proves that locally produced porcelain balls have superior properties than the commercially available porcelain balls.